PERLINDUNGAN HUKUM SAKSI DAN KORBAN SEBAGAI WHISTLEBLOWER DAN JUSTICE COLLABORATORS PADA PENGUNGKAPAN KASUS KORUPSI BERBASIS NILAI KEADILAN - Suratno Suratno (UNISSULA, 2017)
The question of Whistle blower or Justice Collaborator is a complex and interesting issue tobe discussed in a conception or legislation. The role of Whistle Blower and Justice Collaboratorin exposing such extraordinary crimes as corruption is a dilemma, because there is no adequatelegal tool to facilitate the legal guarantee to be obtained. The research approach used in thisresearch is sociological or socio-jurisdiction approach method -legal research. The results of theresearch indicate that: 1. The protection of the witness and victim’s witness law as Whistleblowerand Justice Collaborators on the disclosure of corruption has not been based on the valueof justice, it can be seen that the legal status of a whistle blower does not stop only whistleblowers, Be someone to be held accountable. 2. Legal protection barriers to the existence ofWhistleblower and Justice Collaborators on the disclosure of corruption based on the value ofjustice, known from the side of the substance of the law is the weakness of the arrangement ofJustice collaborator explicitly regulated only in Supreme Court Circular Number 4 of 2011 onthe treatment of rapporteur of acts A Whistleblower and a Justice Collaborator in a particularcriminal case, so that the SEMA does not have a binding legal force as does the Law.